Using Fixation-Related Potentials for Inspecting Natural Interactions - Wobrock, Dennis; Finke, Andrea; Schack, Thomas; Ritter, Helge (Frontiers in Human Neuroscience, 2020)
Brain Computer Interfaces (BCI) offer unique windows into the cognitive processes underlying human-machine interaction. Identifying and analyzing the appropriate brain activity to have access to such windows is often difficult due to technical or psycho-physiological constraints. Indeed, studying interactions through this approach frequently requires adapting them to accommodate specific BCI-related paradigms which change the functioning of their interface on both the human-side and the machine-side. The combined examination of Electroencephalography and Eyetracking recordings, mainly by means of studying Fixation-Related Potentials, can help to circumvent the necessity for these adaptations by determining interaction-relevant moments during natural manipulation. In this contribution, we examine how properties contained within the bi-modal recordings can be used to assess valuable information about the interaction. Practically, three properties are studied which can be obtained solely through data obtained from analysis of the recorded biosignals. Namely, these properties consist of relative gaze metrics, being abstractions of the gaze patterns, the amplitude variations in the early brain activity potentials and the brain activity frequency band differences between fixations. Through their observation, information about three different aspects of the explored interface are obtained. Respectively, the properties provide insights about general perceived task difficulty, locate moments of higher attentional effort and discriminate between moments of exploration and moments of active interaction.